Strategies Used in Translation of Brahmako Prayogshalabata - Ojha, Jay Raj (English Language Teaching Perspectives, 2023)
Brahmako Prayogshalabata, a humorous essay by Bhairab Aryal, is rich in cultural terms and expressions. It may be a challenge for non Nepali readers as well as non-eastern Nepali readers to understand as this humorous essay has been written in eastern Nepali dialect. This essay has been translated in English by Govinda Raj Bhattarai thus his valued work of translation has eased the non Nepali readers as well non -eastern Nepali Readers for acquiring knowledge and insight of reading this essay. This paper aims to explore how the challenges of translating linguistic, pragmatics and cultural terms of native language have been solved while translating into another language. It has adopted corpus- based research design using secondary sources of data and qualitative approach for data analysis and interpretation in order to achieve the set objectives. This paper compares translation of title, words, chunks, culture -specific words and expressions. It concludes that challenges of linguistic, pragmatics and cultural issues can be solved by using the foreignising approach which entails borrowing and literal translation along with substitution, addition, omission, merging, chunking, and expansion of phrases.